Institutional Arbitration in Public Procurement - Guzmán-Barrón Sobrevilla, César (2015)
In the present article, the authors give us an overview about the advantages of institutional arbitration over ad hoc arbitration, on public procurement matter. Thus, starting by describing the present situation of arbitration on that field, they describe the advantages of institutional arbitration, in favor of reaching a more efficient and transparent arbitration system, which is the desired goal.